A switching control method based on a new model considering parasitic capacitance for LLC - Han, Yetong; Ma, Dazhong; An, Qingpeng (Frontiers in Energy Research, 2023)
LLC converters are used for linking renewable energy and smart grids. However, the output is higher than the reference caused by its own characteristics, especially in the light load, and the output is limited. A new control method is proposed in this paper based on a new model considering parasitic capacitance, which plays a vital role in keeping the output constant in the light load conditions and widening the output range. In addition, the definition of the light load is given in this paper, which ensures an accurate control. In the switching process, a transition period is set to avoid the components from being damaged due to sudden switching and ensures a smooth output and the stability of the control. Finally, this control method based on the new model is proved valid on a 400 V-36 V-1 kw prototype.